Labour Landmarks in New Waterford:: Collective Memory in a Cape Breton Coal Town - Mackinnon, Lachlan (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
Labour landmarks enshrine workers’ “public memories” as part of the larger “collective memory” of a community. But these manifestations of working class consciousness are not static. Two monuments in New Waterford (NS) – one to victims of a 1917 mine explosion and the second to William Davis (killed during the 1925 strike) – reveal many layers of historical memory and reflect changing conceptualizations of 20th century labour resistance in Cape Breton amongst the miners, their union, and the town’s citizens.